Primary School Teachers' Views on Teaching Critical Thinking - Serap Yılmaz Özelçi (Revija za Elementarno Izobraževanje, 2023)
The main purpose of the study is to examine the views of classroom teachers on the teaching of critical thinking. It is a qualitative study wherein the data are collected through semi-structured interviews. Thirteen classroom teachers comprised the study group for the research. Descriptive and content analysis is also used in the analysis of the data. According to the findings, teachers believe that critical thinking is a teachable skill, and they know how important their roles are in teaching this skill. However, teachers emphasize that skill training would not be possible without family support.